The Influence of Transformational Leadership and AI-Based Competency Development on Green Innovative Work Behavior: The Mediating Role of Innovation Knowledge Sharing - Reinardus Dwi Prio Christianto; Tri Gunarsih; Agung Hartadi; Ade Setiawan; Arief Dermawan; Ahmad Syarifudin Sukasih (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines the influence of transformational leadership and AI-based competency development on employees’ green innovative work behavior, with innovation knowledge sharing serving as a mediating variable. The research aims to understand how leadership practices and technological competencies can encourage environmentally oriented innovation within organizations. A quantitative research approach was employed using survey data collected from employees through a structured questionnaire. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique to evaluate the relationships among the variables. The findings reveal that transformational leadership significantly influences innovation knowledge sharing and green innovative work behavior. Similarly, AI-based competency development positively affects innovation knowledge sharing and green innovative work behavior. In addition, innovation knowledge sharing has a significant positive effect on employees’ green innovative work behavior. The mediation analysis further demonstrates that innovation knowledge sharing partially mediates the relationships between transformational leadership, AI-based competency development, and green innovative work behavior. These findings highlight the importance of integrating leadership practices, technological competency development, and collaborative knowledge-sharing culture to promote sustainable innovation in organizations. This study contributes to the fields of organizational behavior and innovation management by providing empirical evidence on how leadership and AI-related competencies can foster environmentally oriented innovative behavior among employees in modern organizations.